2016
DOI: 10.1519/jsc.0000000000001362
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Club Head Speed in PGA Professional Golfers

Abstract: Turner, AN. Determinants of club head speed in PGA professional golfers. J Strength Cond Res 30(8): 2266-2270, 2016-Club head speed (CHS) has been significantly correlated with golf performance, but only in amateurs. The purpose of this study therefore, was to investigate the relationship between field-based measures of strength and power with CHS in Professional Golfers Association (PGA) professional golfers, and further determine differences between age groups. A correlation design was used to test relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…the amateur golfers achieved almost identical club head speed with the driver (45.42 m/s) in comparison with a study by Sweeney et al [4], who analysed players of a similar performance level (handicap: 5.7), but lower club head speed than professional golfers (46.85 m/s) described in a study by Lewis et al [24]. Judging by handicap, the participants of this study would be in betzler and Monk's 2 nd performance level category (handicap: 6-12); however, our players also displayed the club head speed that would put them in the 1 st performance category (handicap: 0-5) [1].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…the amateur golfers achieved almost identical club head speed with the driver (45.42 m/s) in comparison with a study by Sweeney et al [4], who analysed players of a similar performance level (handicap: 5.7), but lower club head speed than professional golfers (46.85 m/s) described in a study by Lewis et al [24]. Judging by handicap, the participants of this study would be in betzler and Monk's 2 nd performance level category (handicap: 6-12); however, our players also displayed the club head speed that would put them in the 1 st performance category (handicap: 0-5) [1].…”
Section: Discussionsupporting
confidence: 51%
“…the ball flight results and the impact factors influence amateur players' handicap level, where a lower handicap indicates better performance [1,[19][20][21][22]. Professional players are evaluated by the amount of earnings [6,[23][24][25]. However, performance in both categories can be assessed by the average number of strokes or number of strokes for a single round [26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CMJ height and predicted peak power have shown correlations ranging from moderate to very large with CHS, ball speed, and carry distance (44,56,86,100,109,110). Other jump performance tests used have included the squat jump (SJ) and drop jump with strong to moderate relationships (44,58,86,110). Studies that have used both jump height and/or peak power have indicated that peak power displays stronger correlations than jump height (44,86).…”
Section: Powermentioning
confidence: 99%
“…3) climbing and gymnastics, 4) combat sports, and 5) strength disciplines. INSERT TABLE 3 ABOUT HERE INSERT TABLE ABOUT (3,16,50,62,73,74,86,96,101,103,117,134,137,172,173,176,192,193,197). A comparison of professional baseball players revealed trivial and moderate non-significant HGS differences between the Major League Baseball (MLB©) and minor league baseball ("AAA" and "AA") players, respectively; whereas, moderate and large significant differences were observed between MLB players in comparison to "A" and rookie league players, respectively (76).…”
Section: A C C E P T E Dmentioning
confidence: 99%